History of the United Netherlands, 1592 - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"History of the United Netherlands, 1592" by John Lothrop Motley is a historical account written in the late 19th century. The book primarily focuses on the political and military events in the Netherlands during the late 16th century, particularly the period surrounding the death of William the Silent and extending through the ongoing conflict with Spain. It captures the broader themes of the struggle for independence and the complexities of statecraft during the Dutch Revolt. In this volume, Motley delves into various key military campaigns led by Prince Maurice of Nassau, emphasizing significant sieges such as Steenwyck and Coeworden. The narrative details the tactical innovations introduced in warfare, such as the use of mining and earthworks, alongside the capture of pivotal cities that influenced the outcome of the Eighty Years' War. It also addresses the political dynamics between the Dutch republic and England, showcasing the complexities of their alliance and the grievances that arose from maritime piracy. Through meticulous research and vivid prose, Motley presents a thorough and engaging depiction of a pivotal era in Dutch history, illustrating both the military strategies employed and the broader implications of these conflicts for national sovereignty. (This is an automatically generated summary.)
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648